Use of physical barriers to hamper laying of beetles (Phillophaga spp) in strawberry. - Toledo, Milton (2006)
The effect of coveringstrawerry plants with anti-insect netting and polyethilene filmto hamper laying of beetles on the ground was evaluated fromApril to November of 1998. The coverings were laid over theplants from mid April to mid Juy of 1998, the period of adultactivity in the area. The anti-insect netting was laidpermanently over the plants and was only raised during theday, twice a week (monday and thursday), por cultivationlabors. The ployethylene film was laid over the crop only atnight. The covered plots showed a lower number of grubs(1.6 larvae/m2) a compared to the uncovered plots (23.7larvae/m2). The protected plots lost between 9 and 11% oftheir plants. The plots covered with the net showed 60%more off-shaped fruits thant the unovered plots andpolyethylebe covered plots.